2016
DOI: 10.1038/srep20122
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Chikungunya Virus Replication by 1-[(2-Methylbenzimidazol-1-yl) Methyl]-2-Oxo-Indolin-3-ylidene] Amino] Thiourea(MBZM-N-IBT)

Abstract: Chikungunya virus (CHIKV) infection is one of the most challenging human Arboviral infections with global significance and without any specific antiviral. In this investigation, 1-[(2-methylbenzimidazol-1-yl) methyl]-2-oxo-indolin-3-ylidene] amino] thiourea (MBZM-N-IBT) was synthesised as a molecular hybrid of 2-methyl benzimidazole and isatin-β-thiosemicarbazone and its anti-CHIKV property was evaluated. The release of infectious virus particles was calculated by plaque assay, expression profile of viral RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 51 publications
1
80
0
2
Order By: Relevance
“…For instance, chloroquine has been suggested as a drug with prophylactic and therapeutic effects apparently by impairing endosomal-mediated virus entry during early stages of virus replication [90]. Other anti-parasite agents, such as ivermectin and a benzimidazole-derived drug, have showed effects on replication at early and late stages of infection [91,92]. Doxycycline combined with ribavirin effectively inhibited CHIKV replication and attenuated its infectivity in vivo in animal models [93].…”
Section: Treatment and Antiviral Developmentmentioning
confidence: 99%
“…For instance, chloroquine has been suggested as a drug with prophylactic and therapeutic effects apparently by impairing endosomal-mediated virus entry during early stages of virus replication [90]. Other anti-parasite agents, such as ivermectin and a benzimidazole-derived drug, have showed effects on replication at early and late stages of infection [91,92]. Doxycycline combined with ribavirin effectively inhibited CHIKV replication and attenuated its infectivity in vivo in animal models [93].…”
Section: Treatment and Antiviral Developmentmentioning
confidence: 99%
“…Several compounds have been proposed, including chloroquine (Brighton, 1984), ribavirin (Leyssen et al, 2008), arbidol (Delogu et al, 2017), harringtonine (Kaur et al, 2013), suramina (Albulescu et al, 2015) and silymarin (Lani et al, 2015) that act in different stages of the viral replication cycle, however, have certain disadvantages that make them ineffective for use in CHIKV infections. (Mishra et al, 2016). Mouce et al, 2016a, 2016b showed that PAs, putrescine, spermidine and spermine are important in the replication of a large variety of RNA viruses, including Chikungunya, as well as their participation in other molecular processes such as the packaging of the viral genome; in DNA viruses the polyamines stabilize the negatively charged genome within the virion particle, among them, the bacteriophage T7 virions cytomegalovirus (CMV) (Kalejta, 2008), and vaccinia virus are found (Lanzer, Holowezak., 1975).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 22 distinct benzouracil-coumarin-arene compounds were synthesized, but only 5 were active against CHIKV in Vero cell culture (107). In contrast, distinct elements that had not been shown to have antiviral activity but were projected to be effective in combination by in silico analysis were effective in the case of a thiosemicarbazone with a benzimidazole group attached (109). Unfortunately, while these combination compounds, particularly peptides, are designed to show high specificity and selectivity, they frequently require extensive large-scale production steps, which may limit their manufacturability.…”
Section: Synthesis Of Designer Compoundsmentioning
confidence: 99%